2005
DOI: 10.1113/jphysiol.2004.074799
|View full text |Cite
|
Sign up to set email alerts
|

Autogenic modulation of mechanoreceptor excitability by glutamate release from synaptic‐like vesicles: evidence from the rat muscle spindle primary sensory ending

Abstract: However, excitation by glutamate was abolished by (R,S)-3,5-dihydroxyphenylglycine (DHPG), and rather more effectively by (2R,1 -S,2 -R,3 -S)-2-(2 -carboxy-3 -phenylcyclopropyl)glycine (PCCG-13). PCCG-13 also significantly reduced stretch-activated excitability in the absence of exogenous glutamate. These data indicate that SLVs recycle at rest, releasing glutamate, and that mechanical activity increases this process. The blockade with DHPG and PCCG-13 suggests that endogenous glutamate release acts, at least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
167
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(182 citation statements)
references
References 47 publications
(53 reference statements)
15
167
0
Order By: Relevance
“…Glutamate release can be induced in the periphery following stimulation of A or C sensory afferents (deGroot et al, 2000), and glutamate release from synaptic vesicles has been observed following stretch activation of mechanosensory nerve terminals innervating muscle spindles (Banks et al, 2002;Bewick et al, 2005). Our results strongly suggest that glutamate is crucial for maintaining the sensory capability of the piloneural collar.…”
Section: Discussionmentioning
confidence: 50%
“…Glutamate release can be induced in the periphery following stimulation of A or C sensory afferents (deGroot et al, 2000), and glutamate release from synaptic vesicles has been observed following stretch activation of mechanosensory nerve terminals innervating muscle spindles (Banks et al, 2002;Bewick et al, 2005). Our results strongly suggest that glutamate is crucial for maintaining the sensory capability of the piloneural collar.…”
Section: Discussionmentioning
confidence: 50%
“…However, it is uncertain whether glutamate may be released from the periodontal Ruffini endings and function as a neurotransmitter because glutamate is the most abundant excitatory neurotransmitter in the central nervous system. In the muscle spindles, Bewick et al (2005) proposed that glutamate release has an autogenic effect on excitability of the sensory endings. Thus, similar to the muscle spindle, we speculated that periodontal Ruffini endings released glutamate from axon terminals and this might contribute to the excitability of the endings.…”
Section: Vglut In Ruffini Endingsmentioning
confidence: 99%
“…The dyes then label intracellular membranes, and this labeling is irreversible. However, in hair cells that are not mechanically stimulated 13,14 and in fully differentiated primary sensory nerve terminals in situ, such as Ia endings in muscle spindles 15 , and in the lanceolate endings here 7 , styryl dye labeling seems to reflect membrane endocytosis, since labeling is reversible and does not block the mechanosensory responses 7,15,16 . While some dye internalization by channel permeation in these endings cannot be ruled out completely, it is clear from the continued firing during dye incubation and the reversibility of the labeling that the great majority of the labeling in differentiated terminals in situ is by internalization with recycling vesicle membrane.…”
Section: Discussionmentioning
confidence: 99%